2015
DOI: 10.5433/1679-0359.2015v36n3supl1p2339
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de bovinos inteiros e castrados em sistema intensivo de integração lavoura-pecuária

Abstract: ResumoEste trabalho teve por objetivo avaliar o desempenho de bovinos inteiros ou castrados em um sistema intensivo de integração lavoura-pecuária. O trabalho realizado durante os anos de 2004 e 2005, foi conduzido na Fazenda Experimental da Cooperativa Agropecuária Mourãoense -COAMO, situada no município de Campo Mourão, Paraná. O delineamento experimental utilizado foi o inteiramente ao acaso, com dois tratamentos, inteiros ou castrados. Foram utilizados 40 machos mestiços, ½ Angus+½Nelore, com idade média i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
3
0
4
Order By: Relevance
“…The forest plot indicated a similar result (Figure 2), but with a tendency of immunocastrated steers presenting SFD 0.79 mm greater than that of non-castrated animals, but similar to that of the surgically-castrated group. This corroborates the work of Turini et al (2015), who found that the deposition of adipose tissue is delayed in the meat of non-castrated animals, as they complete their muscle development later than the castrated ones.…”
Section: Resultssupporting
confidence: 92%
“…The forest plot indicated a similar result (Figure 2), but with a tendency of immunocastrated steers presenting SFD 0.79 mm greater than that of non-castrated animals, but similar to that of the surgically-castrated group. This corroborates the work of Turini et al (2015), who found that the deposition of adipose tissue is delayed in the meat of non-castrated animals, as they complete their muscle development later than the castrated ones.…”
Section: Resultssupporting
confidence: 92%
“…This fact may be related to the breed's effectiveness in terms of feed conversion and ADG. In addition, it is known that whole animals have a higher rate of weight gain, especially during the great development phase (TURINI et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Ao trabalharem com búfalos da raça mediterrâneo inteiros e castrados criados a pasto Ramalho et al (2013) RESTLE et al, 1996;TURINI et al, 2015 Em relação às medidas e aos aumentos absolutos e relativos entre peso e medidas de abertura de ísquio, largura de ílio, não foram encontradas diferenças (P>0,05) entre animais inteiros e castrados (Tabelas 2, 3). A similaridade em se tratando de abertura de ísquios e largura de ílios é indicativo de semelhança no que diz respeito aos principais cortes nobres da carcaça, considerando que os mesmos se encontram em sua maioria no quarto traseiro (MOURÃO et al, 2010), sendo o estudo destas variáveis importante, pois na região da garupa encontram-se alocados os cortes com maior valor comercial (PASCOAL et al, 2010).…”
Section: Resultsunclassified
“…O desempenho animal pode ser influenciado pelo sexo ou condição sexual (TURINI et al, 2015), idade do animal (FRENEAU et al, 2008;KUSS et al, 2008), alimentação e ou sistema de criação (PACHECO et al, 2008, REZENDE et al, 2011, BARROS et al, 2016, raça ou grupo genético (VITTORI et al, 2006;PINHEIRO et al, 2009), tamanho animal (CASTILHO et al, 2018;FARIAS et al, 2018ab) e o uso de promotores de crescimento ou anabolizantes (BELTRAME, 2013).…”
Section: Introductionunclassified